The Objectiveness of The Alleged Victims as A Parameter for Law Enforcement in A Defamation Case - Emmilia Rusdiana (Faculty of Law, Maranatha Christian University, 2023)
Activities in the complaints form from victims who feel libel by others have increased and occurred at all levels of the police in Indonesia. Everyone can feel offended by different insults, so the law enforcement of criminal offenses based on Article 310 paragraph (3) of the Criminal Code requires objectivity to accusations of defamation. The research points to a detriment as the basis for defamation, it is the concrete form of this detrimental requires further study as a manifestation of the substitute for defamation in the public interest. This article aims to validate the objectivity of the victim's alleged insult and defamation allegations. Article uses normative research type and conceptual approach with qualitative analysis. The defamation case regarding the meaning of the public interest. Justice is a baseline with the realization in concrete situations. The interest form of the community through the property by demanding actions that are proportional, appropriate, balanced, and in harmony with the rights of everyone. An emphasis on values prevailing in society (morals and customs). There are direct interests that are primarily economic. Then, the basis for filing a victim's complaint requires concrete evidence of the consequences of the alleged defamation, namely losses. Calculation of Losses. The specific requirement is that material or immaterial loss arise during the pre-contractual, contractual, and post-contractual periods. The complainant or victim must show the contract between the complainant and the offender.